Determination of Barriers in Medication Adherence for Secondary Prevention in Stroke Patients - Velusamy, Sivakumar; Varatharaj, Kanishya; Kathirvel, Rasika; Venkatesan, Pavithra; Varghese, Leah Jayan (Journal of Pharmacy Practice and Community Medicine)
Background: It is a challenge for healthcare professionals to ensure that patients adhere to their medications. Although medications are more effective in reducing the risk of recurrent strokes, adherence to long-term treatment is low. The identification of barriers preventing medication adherence is therefore necessary to ensure optimal treatment. Our study aims to determine the barriers in medication adherence for secondary prevention in patients with ischemic stroke. Materials and Methods: A prospective study done in the Department of Neurology, PSG Hospitals, Coimbatore, India. 132 patients who received secondary prevention treatment for ischemic stroke were included in the study. Results: The patients were grouped into high, medium and low adherent categories. None of them had low adherence, 9.09% showed medium adherence and 90.9% of them fell into the high adherence category despite experiencing barriers. The following factors significantly reduced the medication adherence: worry about taking medication for a long time (52.3%, p=0.001), stopping medicines when feeling better (38.6%, p=0.000), stopping medicines intentionally (34.1%, p=0.000), white coat adherence (11.4%, p=0.000), forgetfulness (43.2%, p=0.000), frequency (9.1%, p=0.000), confusion in taking medicines (9.1%, p=0.000), number of medications (31.8%, p=0.000), difficulty to access hospital (36.4%, p=0.004) and difficulty in understanding the doctor(2.3%, p=0.000). Conclusion: It is important to identify the barriers to medication adherence and to resolve them at the earliest to avoid recurrent stroke. Among the significant barriers, the most important one was worrying about taking medications for a long time. Therefore, healthcare professionals, caregivers, and patients should work together to enhance medication adherence.
Keywords: Recurrent stroke; Barriers; Medication adherence; Secondary prevention